2018
DOI: 10.1016/j.smrv.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and behavioral therapies in the treatment of insomnia: A meta-analysis

Abstract: Insomnia is a major public health problem considering its high prevalence, impact on daily life, co-morbidity with other disorders and societal costs. Cognitive behavioral treatment for insomnia (CBTI) is currently considered to be the preferred treatment. However, no meta-analysis exists of all studies using at least one component of CBTI for insomnia, which also uses modern techniques to pool data and to analyze subgroups of patients. We included 87 randomized controlled trials, comparing 118 treatments (372… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
287
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 485 publications
(343 citation statements)
references
References 135 publications
22
287
1
5
Order By: Relevance
“…Outside the field of rheumatic diseases, meta-analyses support the effectiveness of behavioural, including self-help, interventions on sleep outcomes 41 42. Face-to-face treatments of at least four sessions seem to be more effective than self-help interventions 43. In meta-analyses, small but significant effects of sleep interventions on pain have been observed in people with varied chronic medical conditions 44 45…”
Section: Resultsmentioning
confidence: 99%
“…Outside the field of rheumatic diseases, meta-analyses support the effectiveness of behavioural, including self-help, interventions on sleep outcomes 41 42. Face-to-face treatments of at least four sessions seem to be more effective than self-help interventions 43. In meta-analyses, small but significant effects of sleep interventions on pain have been observed in people with varied chronic medical conditions 44 45…”
Section: Resultsmentioning
confidence: 99%
“…57 CBTi is the recommended preferred treatment for insomnia; 58 a meta-analysis of 87 randomized controlled trials found CBTi to be useful in patients with and without comorbid disease. 59 Specifically in CM, a small pilot study, not included in the meta-analysis, showed that in women, behavioral sleep modification resulted in reduced headache frequency and reversion to EM. 60 Similarly, in individuals with CM, behavioral treatment of comorbid insomnia yielded reductions in headache frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive behavioral therapy for insomnia (CBT-I) is recommended as a first-line treatment for adult insomnia 23 , based on evidence from multiple systematic reviews and meta-analyses that the intervention improves sleep and mental health in adults, with small to medium effect sizes. [24][25][26][27] However, only nine trials have evaluated the efficacy of cognitive behavioral sleep interventions among adolescents. Two were randomized controlled trials (RCTs) 28,29 , one was a prospective RCT 30 , and six were uncontrolled feasibility trials.…”
Section: Statement Of Significancementioning
confidence: 99%
“…As with adults, improvements tended to be stronger for wakefulness in bed variables compared to sleep duration variables and self-reported sleep variables compared to objective sleep variables. [24][25][26] However, the trials were limited in several ways, including small sample sizes [31][32][33][34][35][36] , lack of control groups [31][32][33][34][35][36] , wait-list control groups 28,29 , high attrition rates 29,32 , lack of follow-ups 31,34 , short follow-ups 28,35,36 , and/or reliance of self-reported measures of sleep. 29,33,34 The SENSE study is an RCT investigating whether a 7-week, cognitive behavioral, and mindfulness-based group sleep intervention can prevent the emergence of major depressive disorder (MDD) at 2-year follow-up among a group of adolescents (aged 12-17 years) who were experiencing elevated levels of sleep problems and anxiety symptoms.…”
Section: Statement Of Significancementioning
confidence: 99%